Development of an Islamic Community Model Based on Local Wisdom in Bandar Khalifah Village - Lubis, Muhammad Bagas Ansari; Muin, Mohd. Iqbal Abdul (Prodi Studi Agama-Agama, 2026)
This study aims to develop an Islamic community model based on local wisdom in Bandar Khalifah Village, Percut Sei Tuan District, Deli Serdang Regency. The research focuses on analyzing how local cultural values are integrated with Islamic teachings to strengthen religious identity, enhance social solidarity, and improve community welfare. It also examines the roles of key social actors and identifies the challenges encountered in implementing the model. This research employs a descriptive qualitative approach, with data collected through participatory observation, in-depth interviews with ten informants (including religious leaders, traditional leaders, village officials, and community members), and documentation studies. The data were analyzed using thematic analysis to identify patterns of strategies and social dynamics. The findings reveal that the Islamic community development model is constructed through the integration of Islamic values such as ukhuwah Islamiyah (Islamic brotherhood), ta’awun (mutual assistance), and shura (deliberation) with local wisdom practices, including kenduri (communal feasts), gotong royong (mutual cooperation), village deliberation, and regular religious gatherings. This integration strengthens social cohesion and fosters a harmonious and inclusive religious environment. Religious leaders and Islamic educational institutions play a significant role as facilitators in transforming local wisdom into effective instruments of da'wah. However, the model faces several challenges, including the impact of modernization that gradually erodes traditional practices, shifting values among younger generations, and the lack of formal documentation of local wisdom. This study contributes to the formulation of a contextually relevant Islamic community development model for rural settings